2005
DOI: 10.1248/bpb.28.1971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitobiose and Chitotriose on Carbon Tetrachloride-Induced Acute Hepatotoxicity in Rats

Abstract: The purpose of the present study was to examine whether chitobiose and chitotriose can protect rats from CCl 4 -induced hepatic toxicity when given orally. We studied the effects of the 2 chitooligosaccharides given orally to rats on the acute hepatotoxicity induced by CCl 4 -dependent lipid peroxidation. The increase in the sum of malondialdehyde and 4-hydroxy-2-alkenals, a marker of lipid peroxidation, in both plasma and liver of CCl 4 -treated rats was suppressed by oral administration of chitobiose or chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…Increased lipid peroxidation and impaired antioxidant enzyme function in the liver tissue are characteristic observations in PCM-treated rats (Weber et al, 2003). In the present study, MDA concentration significantly increased (p ˂ 0.05) 24hr after PCM treatment alone as demonstrated in other studies (Ohta et al, 1997;Chen et al, 2005).This elevated level of MDA in plasma or liver tissue caused by PCM treatment was significantly depressed by the pretreatment with ghrelin. This was attributed to the decreased bioactivation of PCM caused by the ghrelin pretreatment.…”
Section: Discussionsupporting
confidence: 83%
“…Increased lipid peroxidation and impaired antioxidant enzyme function in the liver tissue are characteristic observations in PCM-treated rats (Weber et al, 2003). In the present study, MDA concentration significantly increased (p ˂ 0.05) 24hr after PCM treatment alone as demonstrated in other studies (Ohta et al, 1997;Chen et al, 2005).This elevated level of MDA in plasma or liver tissue caused by PCM treatment was significantly depressed by the pretreatment with ghrelin. This was attributed to the decreased bioactivation of PCM caused by the ghrelin pretreatment.…”
Section: Discussionsupporting
confidence: 83%
“…agreement with the findings of Boll et al 36 and Chen et al 37 Boll et al 36 explained that the trichloromethyl radicals generated during the biotransformation of CCl 4 bind triacylglycerol and phospholipid, with phosphatidylcholine binding being the highest; the binding therefore promotes the peroxidation of these lipids. The ability of KV, FI, FII, and vitamin E to attenuate the toxic assault imposed on lipids by CCl 4 points to either their free radical-chain breaking or scavenging activities.…”
supporting
confidence: 88%
“…It is known that chitosan is not to be absorbable by orally administration on account of only chitobiose or chitotriose can be absorbed by the digestive tract among various chitooligosaccharides (Chen et al, 2005). In previous study, 85% of FITC-CM-chitosan was excreted in urine within 11 d. Our present work showed that through the intraperitoneal injection of FITC-HP-chitosan at a dose of 10 mg per rat, 98.62% of the content was rapidly absorbed in 24 h, 88.47% was excreted in urine within 11 d. The GPC analysis in vivo and in vitro also indicated that a significant degradation process occurred in abdominal cavity, plasma and liver.…”
Section: Discussionmentioning
confidence: 99%